Built to win? Exploring the role of competitive environments on students' creativity in design for additive manufacturing tasks. (1st December 2020) - Prabhu, Rohan; Miller, Scarlett R.; Simpson, Timothy W.; Meisel, Nicholas A.
Abstract : Designers skilled in design for additive manufacturing (AM, DfAM) must apply restrictive DfAM to prevent build failure and opportunistic DfAM to leverage AM capabilities. Few studies have explored the effect of students' motivation on the outcomes of DfAM education. The experiment in this article introduced engineering students to either restrictive or dual (opportunistic and restrictive) DfAM followed by a design task, either presented as a showcase (results presented to the rest of the class) or as a competition (best performing design would be rewarded). Students trained in dual DfAM generated more creative ideas compared to restrictive DfAM – but only when presented with the competitive design task. These results help educators develop design tasks that encourage the creative application of DfAM.